1995
DOI: 10.1200/jco.1995.13.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of reduced glutathione on cisplatin-based chemotherapy in advanced gastric cancer: a randomized double-blind placebo-controlled trial.

Abstract: This study provides evidence that GSH is a promising and effective new drug for the prevention of CDDP-induced neuropathy, and that it does not reduce the clinical activity of chemotherapeutic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
1
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(105 citation statements)
references
References 0 publications
2
96
1
5
Order By: Relevance
“…clutathione and bone marrow support w-ith the haematopoietic growth factor filgrastim determined objectixe responses in 25 of 34 advanced gastric cancer patients Nx-ith a mild toxicitx (Cascinu et al 1993 Glutathione was gixen at a dose of 1.5 m-in 100 ml of normal saline ox er 15 min immediately before each CDDP administration to prevent CDDP-associated neurotoxicity as indicated by our previous experience (Cascinu et al 1995). Standard intraxvenous hydration was used: 2 h before initiation of the CDDP infusion.…”
Section: Epidoxorubicin (Epiadr) Cisplatin (Cddp)mentioning
confidence: 99%
“…clutathione and bone marrow support w-ith the haematopoietic growth factor filgrastim determined objectixe responses in 25 of 34 advanced gastric cancer patients Nx-ith a mild toxicitx (Cascinu et al 1993 Glutathione was gixen at a dose of 1.5 m-in 100 ml of normal saline ox er 15 min immediately before each CDDP administration to prevent CDDP-associated neurotoxicity as indicated by our previous experience (Cascinu et al 1995). Standard intraxvenous hydration was used: 2 h before initiation of the CDDP infusion.…”
Section: Epidoxorubicin (Epiadr) Cisplatin (Cddp)mentioning
confidence: 99%
“…Witschi et al administered a single oral dose of up to 3 g of GSH to seven healthy subjects and did not observe an increase in blood GSH levels, concluding ''it is not feasible to increase circulating GSH to a clinically beneficial extent by the oral administration of 3 g of GSH.'' 22 Yet three studies have evaluated the impact of reduced GSH supplementation combined with oxidative chemotherapeutic agents in patients with various cancers [23][24][25] ; all three trials demonstrated reduced adverse effects of the chemotherapy without negative effects on the effectiveness of the regimen, suggesting some physiologic effect from oral dosing. Unfortunately GSH status was not measured in any of these trials.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, glutathione, N-acetylcysteine, and vitamin E (a-tocopherol) may have a clinical role in patient neuroprotection. 4,6,7,25,29,35 However, the major bias of these clinical trials resides in their small size and/ or in their short term follow-up. 2 An important limit in this field is the insufficient information on the molecular basis of the neuropathy.…”
mentioning
confidence: 99%